CN bond orientation in metal carbonitride endofullerenes：A density functional theory study - 张竹霞;张勇;薛文华;贾伟;张彩丽;李春霞;崔鹏 (Chinese physics B, 2017)
The geometric and electronic structures of scandium carbonitride endofullerene Sc3CN@C2n （2n=68, 78, 80, 82, and 84） and Sc（Y）NC@C76 have been systematically investigated to identify the preferred position of internal C and N atoms by density functional theory （DFT） calculations combined with statistical mechanics treatments. The CN bond orientation can generally be inferred from the molecule stability and electronic configuration. It is found that Sc3CN@C2n molecules have the most stable structure with C atom locating at the center of Sc3CN cluster. The CN bond has trivalent form of[CN]3- and connects with adjacent three Sc atoms tightly. However, in Sc（Y）NC@C76 with[NC]-, the N atom always resides in the center of the whole molecule. In addition, the stability of Sc3CN@C2n has been further compared in terms of the organization of the corresponding molecular energy level. The structural differences between Sc3CN@C2n and Sc3NC@C2n are highlighted by their respected infrared spectra.